Validity and reliability of the step test to estimate maximal oxygen consumption in pediatric population - Gerardo Weisstaub; José González; Ignacio Orizola; Juan Borquez; Matías Monsalves-Alvarez; Lydia Lera; Rodrigo Troncoso; Carlos Sepúlveda (Scientific Reports)
Abstract Cardiorespiratory fitness is the most important variable related to health and a strong predictor of mortality. However, it is rarely used in clinics due to costs, specialized equipment, space needs, and the requirements of expert staff such as an exercise physiologist, physician, or other health professional. This work aims to validate and test the reliability of a submaximal step test to estimate VO2max of 8-to 16-year-old pediatric populations as a simple and low-cost tool for clinical practice. A cross-sectional study included 242 children and adolescents (42.1% girls) aged 8–16. Cardiorespiratory fitness was determined by a maximal incremental test on a treadmill until exhaustion. The step test entailed maintaining a steady pace of 22 steps per minute for 3 min (60 bpm), with the heart rate being recorded at the end of the test. Nutritional status was computed through BMI z-score. A multiple linear regression model validated the step test and developed a new equation to predict VO2max, including the third-minute heart rate, weight, and height. The reliability among predicted and measured VO2max was assessed by Bland-Altman analysis. The mean age was 12.5 ± 2.6; 51.6% were overweight or obese. The cardiorespiratory fitness measured as VO2max was 35.01 ± 0.58 ml·min-1·kg−1. A robust correlation was observed between the predicted VO2max from the step test and the measured VO2max (r = 0.86, p < 0.001). Bland-Altman analysis indicated statistical concordance between predicted and measured VO2max. Our findings indicate that the step test protocol is valid and reliable for estimating VO2max in children and adolescents. Furthermore, the predictive equation is suitable for application among children aged 8–16.